Pengaruh Pemberian Zpt Giberelin Dan Auksin Terhadap Pertumbuhan Dan Hasil Stek Tanaman Kentang Varietas Granola Arjuno (Solanum tuberosum L.) - Windhy May Wulan Sari; Anis Rosyidah; Siti Muslikah (AGRONISMA, 2021)
The third most important food crop in the world after rice and wheat is potato (Solanum tuberosum L.) (CIP, 2010). tuber plants that are rich in carbohydrates and their needs continue to increase. The addition of ZPT such as auxin and gibberellin is one of the superior techniques for procuring potato seeds because it accelerates cell division and elongation, regulates the growth of roots, stems, and fruit. This study aims to determine the effect of ZPT (growth regulator) auxin and gibberellin on plant growth and yield. This research was conducted in the screen house of Sumber Brantas village. The design used in this study was a randomized block design (RBD) with the treatment given, among other things, P0: without giving ZPT, PI. giving ZPT gibberellin 10ml / l liter of water, P2: giving ZPT auxin 10ml / l liter of water, P3: giving ZPT 5ml auxin * 5ml gibberellin / l liter of water. The parameters observed were: stem height, stem diameter, number of stems, number of leaves, number of tubers, fresh weight of plant tubers, tuber diameter of the plant. The results of this study indicate that the P3 treatment (giving ZPT auxin 5inl and gibberellin 5ml / liter of water) gave the best results on plant growth and crop yield with tuber diameter yields of 21.56 mm. There is a tuber 3.67 grams, fresh weight 29.46 grams.